PENGUATAN KAPASITAS ANGGOTA PKK MELALUI KEWIRAUSAHAAN BERBASIS MANAJEMEN KEUANGAN DI KELURAHAN PRINGREJO PEKALONGAN - Sutapa; Rustam Hanafi (LPPM Universitas Abdurrab, 2025)
Financial management is the process of planning, organizing, controlling, and monitoring the financial resources of a business or organization to achieve predetermined goals. In the context of MSMEs (Micro, Small, and Medium Enterprises), including batik MSMEs such as those in Pringrejo Village, financial management is very important so that businesses can run healthily, efficiently, and develop sustainably. The purpose of this community service is to improve the understanding of PKK members about the basics of entrepreneurship, improve household and business financial management skills and foster an entrepreneurial spirit and economic independence. MSME groups consisting of several business actors still face a number of obstacles, one of which is the lack of understanding in managing finances and recording bookkeeping properly. This community service activity aims to increase the economic capacity of the group through assistance in financial management and bookkeeping. The methods used include assistance and capacity building with a training and advocacy approach. The target number of participants is 35 MSME actors and the training is carried out for 1 day, assistance for 1 month. The results are that business actors who are members of the MSME group have a better understanding and are more proficient in their accounting records.